2017
DOI: 10.12913/22998624/70996
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Post-Processing on Accuracy of FDM Products

Abstract: This paper presents the assessment of the rapid prototyping finishing techniques for printed components. The aim of the study was to compare the element printed with FDM technology before and after the treatment, using 3D scanning techniques. The object was scanned right after manufacturing, then it was subjected to finishing treatment and 3D-scanned again. The assessment of the results was performed using the GOM Inspect software, based on a comparison between scans and nominal model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…A reduction in the tensile strength of Hyrem 30 M 3D printed ABS was observed after the shot peening process. [ 141 ] Kuczko et al [ 142 ] demonstrated the capability of the sanding process in improving the surface quality of FFF 3D printing by reducing the stair‐case effect developed in layered manufacturing processes. Large time consumption was a major limitation of this post‐processing method.…”
Section: Post‐processing Techniquesmentioning
confidence: 99%
“…A reduction in the tensile strength of Hyrem 30 M 3D printed ABS was observed after the shot peening process. [ 141 ] Kuczko et al [ 142 ] demonstrated the capability of the sanding process in improving the surface quality of FFF 3D printing by reducing the stair‐case effect developed in layered manufacturing processes. Large time consumption was a major limitation of this post‐processing method.…”
Section: Post‐processing Techniquesmentioning
confidence: 99%
“…In addition, few studies show the impact of these treatments on other material properties. Chemical treatments can significantly alter the nature of the material and, together with it, the complete functionality of the piece [21,22]. Specifically, PLA presents an unusually wide range of properties between its amorphous state and its crystalline state.…”
Section: Introductionmentioning
confidence: 99%
“…Among the “green” polymers, thermoplastic starch, polyhydroxyalkanoate and poly(butylene adipate‐co‐terephthalate) are among the most common, and poly(lactic acid) (PLA) is the most popular biodegradable and plant‐based resin . PLA is extensively researched and finds many industrial applications, including various food packages, bottles, consumer goods, automotive parts, biomedical applications, and 3D printing filaments . However, apart from its obvious advantages, such as good mechanical strength and processability, PLA also has several drawbacks that should be overcome to further develop its application possibilities.…”
Section: Introductionmentioning
confidence: 99%